Online Sexual Solicitation - Kate Fogarty (EDIS, 2012)
“Internet connectivity in the form of blogs, chat rooms, and forums can be hazardous to our teens today. These online communication aids are not themselves the problem; rather, teens face an ever-present threat of being sexually solicited online.” This 2-page Family Album Radio transcript was written by Kate Fogarty and published by the UF Department of Family, Youth and Community Sciences, March 2012.